Flexible ureteroscopy with and without ureteral access sheath in treatment of large renal stones: a randomized controlled study - Waheed Fawzy Abdelrasol; Ahmed Assem (African Journal of Urology)
Abstract Background In flexible ureteroscopy (FURS), the ureteral access sheath (UAS) is extensively used due to its superior stone-free rates and reduced intrarenal pressure. However, it may cause damage to the ureteral wall and increase surgery costs. Therefore, we aimed to compare the safety and effectiveness of FURS with and without UAS in treating renal stones. Methods This randomized controlled trial included 84 patients with upper ureteric and kidney stones undergoing FURS. Patients were randomized into two equal groups: Group I FURS treated with UAS and Group II FURS treated without UAS as a control group. Results Operative time was significantly delayed in Group I 69.52 ± 14.52 min as opposed to Group II 63.1 ± 9.69 min (p = 0.019). Cumulative stone size exhibited significantly greater values in Group I than Group II (p value < 0.001). The need for ancillary procedures was significantly higher in Group I than in Group II (p value = 0.047). Preoperative and postoperative stent, complications, renal colic pain, urinary tract infection, and length of stay were insignificantly different among the two groups. Conclusions Performing FURS without utilizing UAS appears safe and requires fewer additional procedures. Another benefit is the reduction in surgical duration and avoiding ureteral complications.